Infantile Myofibroma: A Series of 2 Cases with Special Reference to Cytological Features. (4th July 2022) - Dey, Soumya; Khatun, Farjana; Ray, Raktim; Barman, Shibsankar; Chatterjee, Uttara
Abstract: Background Infantile myofibromas (IM) are benign soft tissue lesions of childhood and represent a significant portion of the benign spectrum of fibroblastic-myofibroblastic tumors. Cytological diagnosis of these tumors can be challenging because of overlapping morphology and limited case report descriptions. We describe the cytological features and the cytological differential diagnoses. Case report We describe cytological features of two IMs. The main features were the presence of loose clusters and dispersed bland myofibroblasts in varying stages of maturation with traversing blood vessels and myxoid stroma. The cells typically lacked features of atypia, mitoses and significant pleomorphism. Conclusion Diagnosis of IM on the basis of cytology alone can be tricky and definitive diagnosis should be made only after correlating the cytological features with histology. However, bland morphology of differentiating myofibroblasts can aid in cytological diagnosis and help to exclude other malignant spindle cells neoplasms needing preoperative chemotherapy.